Taking advantage of near-field heating in order to increase ablated volume during high intensity focused ultrasound - Damianou, Christakis A.; Komodromos, M.; Koupis, A.; Curiel, Laura; Chapelon, Jean Yves (My University, 2006)
The goal of the study was to suggest ultrasonic parameters that take advantage of near-field heating in order to increase the volume of the ablated tissue and consequently reducing the total time of high intensity ultrasonic ablation. The main parameter evaluated as an indicator of producing controlled lesions was the ratio of width of necrosis at the focal region over the width of necrosis in the near-field (WI/WN). A W I/WN close to 1 indicated a good reflection of the focal heating, meaning that the lesion was controlled and could be used to increase the ablated volume. The most significant ultrasonic parameter that reduced the treatment time was the delay between successive ultrasonic firings. It was found that at a spatial in situ intensity close to 1000 W/cm2, the W I/WN is close to 1 even with a delay between successive ultrasonic firings as low as 10 s (transducer T1: 50 mm diameter, 40 mm radius of curvature, and frequency of 3 MHz). The lower the intensity or the higher the delay, the closer to unity is WI/WN. For a different transducer (T2: 40 mm diameter, 40 mm radius of curvature, and frequency of 3 MHz) the WI/WN was lower, indicating that the transducer geometry can play an important role for producing controlled lesions in the near-field. However, the same concepts were also observed for both geometries. This technique of increasing the ablated volume was verified in turkey tissue in vitro. The effect of other parameters such as frequency, focal depth and area of the grid pattern on is still under investigation. © 2006 American Institute of Physics.
Keywords: Ablation volume; IFU; Near-field heating